Prognostic significance of nutritional status for neurological and functional recovery after cervical spinal cord injury - Momo Irie; Kazuya Yokota; Tomoya Matsunaga; Osamu Kawano; Muneaki Masuda; Kensuke Kubota; Yuto Ariji; Ryuichiro Koga; Hiroaki Sakai; Takeshi Maeda; Yasuharu Nakashima; Tetsuo Hayashi (PLoS ONE, 2026)
Cervical spinal cord injury (SCI) often results in severe motor and sensory deficits, leading to substantial impairment in activities of daily living. Malnutrition is common after SCI and may adversely affect recovery; however, the association between early nutritional status and subsequent neurological and functional recovery remains unclear. This study examined the association between early nutritional status and neurological and functional recovery after acute traumatic cervical SCI. Ninety-one patients admitted within 72 hours of injury and followed for at least 6 months were retrospectively analyzed. Neurological function was assessed using the International Standards for Neurological Classification of Spinal Cord Injury (ISNCSCI) total motor score, and functional independence was evaluated using the Spinal Cord Independence Measure version Ⅲ (SCIM Ⅲ). Nutritional status after SCI was assessed using the Prognostic Nutritional Index (PNI), Geriatric Nutritional Risk Index (GNRI), and Controlling Nutritional Status (CONUT) score. Recovery rates were calculated as the proportion of the maximum possible improvement achieved between 4 weeks and 6 months after SCI. Patients with higher PNI at 4 weeks after SCI showed greater neurological and functional recovery. Mean ISNCSCI total motor score recovery rates were 43.89%, 28.08%, and 18.7% in the good, normal, and poor PNI groups, respectively (p for trend = 0.0005), with corresponding SCIM III recovery rates of 40.65%, 26.1%, and 22.41% (p for trend = 0.0072). GNRI and CONUT scores were also associated with ISNCSCI total motor score recovery; however, PNI showed the strongest predictive performance (p = 0.0031). In multivariable linear regression analyses adjusting for age, sex, and baseline neurological and functional status, PNI remained independently associated with ISNCSCI total motor score recovery (β = 0.857 per 1-point increase, 95% CI 0.011–1.703, p = 0.0471). These findings indicate that early nutritional status, particularly as assessed by the PNI, is independently associated with neurological recovery after cervical SCI and may be useful for early prognostic assessment.